2015
DOI: 10.1186/s13068-015-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional program for nitrogen starvation-induced lipid accumulation in Chlamydomonas reinhardtii

Abstract: BackgroundAlgae accumulate lipids to endure different kinds of environmental stresses including macronutrient starvation. Although this response has been extensively studied, an in depth understanding of the transcriptional regulatory network (TRN) that controls the transition into lipid accumulation remains elusive. In this study, we used a systems biology approach to elucidate the transcriptional program that coordinates the nitrogen starvation-induced metabolic readjustments that drive lipid accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 109 publications
2
27
0
Order By: Relevance
“…stationary phase). Surprisingly, the transcriptome profile of D. tertiolecta – specifically the upregulation of CCM genes contributing to the supply of acetyl-CoA and NADPH – were vastly similar to oleaginous microalgae including N. oceanica 7 and C. reinhardtii 47. The increased transcript levels of TCA cycle genes and genes contributing to reducing power such as G6PDH and ME were correspondingly observed in heterotrophic fungi such as Mortierella alpina 48 and Mucor circinelloides 4950 to be critical determinants of lipid synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…stationary phase). Surprisingly, the transcriptome profile of D. tertiolecta – specifically the upregulation of CCM genes contributing to the supply of acetyl-CoA and NADPH – were vastly similar to oleaginous microalgae including N. oceanica 7 and C. reinhardtii 47. The increased transcript levels of TCA cycle genes and genes contributing to reducing power such as G6PDH and ME were correspondingly observed in heterotrophic fungi such as Mortierella alpina 48 and Mucor circinelloides 4950 to be critical determinants of lipid synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, many TFs related to photosynthetic carbon fixation such as MYB-related TFs is up-regulated with the same pattern across developmental phases. It has been demonstrated that Myb-related transcription factor is involved in phytochrome signal transduction pathway leading to upregulation of lchb (light-harvesting chlorophyll b) gene in Arabidopsis [38,39] Transcriptional regulators (TRs) are at the interface between sensing and responding to environmental conditions [40]. Results indicated that GNAT (GCN5-related-N-acetyltransferase), SNF2 (sucrose non-fermenting 2), and SET families are top classes of TRs at three phases (S3 Table).…”
Section: Identification Of the Transcription Factors (Tfs) Transcripmentioning
confidence: 99%
“…We advocate for integrated microbial community models that include gene regulation across time. Along with other successful efforts in gene regulatory network inference (Desai et al, 2017;Chan et al, 2017;von Dassow et al, 2000;Liu et al, 2016), environmental gene regulatory influence network (EGRIN) models have broadly been used to predict cellular phenotypic states from single species (Yoon et al, 2013;Ashworth et al, 2013;Bonneau et al, 2007;Peterson et al, 2014;López García de Lomana et al, 2015;Brooks et al, 2014). The goal of creating EGRIN models for denitrifying organisms is to highlight key regulatory pathways and environmental determinants affecting the production and consumption of N 2 O.…”
Section: Laboratory-based Studies To Gain Mechanistic Understanding Omentioning
confidence: 99%